The relationship between insulin resistance and fibroblast growth factor 23 in patients with non-diabetic pre-dialysis chronic kidney disease: a cross-sectional study - Beyza Algul Durak; Melahat Coban (São Paulo Medical Journal)
ABSTRACT BACKGROUND: Insulin resistance often occurs in patients with chronic kidney disease (CKD) owing to mineral and bone metabolism disorders. Fibroblast growth factor (FGF)-23 and soluble klotho (s-KL) play crucial roles in linking CKD with mineral and bone metabolism. OBJECTIVE: This study aimed to examine the relationship between insulin resistance and FGF-23 and s-KL in patients with non-diabetic pre-dialysis patients with CKD. DESIGN AND SETTING: This research was conducted in the Ankara Bilkent City Hospital Nephrology Clinic. Ankara,Turkey. METHODS: This study included 133 male and 150 female patients with pre-dialysis CKD. The patients were compared with 80 healthy individuals. FGF-23 and s-KL levels were determined using enzyme-linked immunosorbent assay kits. The homeostasis model assessment of insulin resistance (HOMA-IR) was used to determine insulin resistance. RESULTS: Creatinine, urine protein/creatinine ratio (UPCR), log10 FGF-23, log 10 s-KL, and HOMA-IR were notably higher, while glomerular filtration rate was notably lower, in patients than in healthy individuals. Stage 5 CKD, log10 FGF-23, creatinine, and UPCR were significantly higher in patients with HOMA-IR > 3.06 compared to those with HOMA-IR ≤ 3.06. No difference was observed in s-KL levels between the two groups. Univariate and multivariate logistic regression analyses revealed an increase in HOMA-IR and log10 FGF-23 values. CONCLUSIONS: Insulin resistance, serum FGF-23, and s-KL levels increased in patients compared with healthy individuals. Higher creatinine, proteinuria, and FGF-23 levels were associated with greater insulin resistance. The study highlighted a significant relationship between insulin resistance and FGF-23.